Sofosbuvir plus ribavirin in treatment‐naïve patients with chronic hepatitis C virus genotype 1 or 3 infection in India. Issue 5 (9th December 2016) - Shah, S. R.; Chowdhury, A.; Mehta, R.; Kapoor, D.; Duseja, A.; Koshy, A.; Shukla, A.; Sood, A.; Madan, K.; Sud, R.; Nijhawan, S.; Pawan, R.; et al.
Summary: Until 2014, pegylated interferon plus ribavirin was the recommended standard of care for the treatment of chronic hepatitis C virus (HCV) infection in India. This open‐label phase 3b study, conducted across 14 sites in India between 31 March 2014 and 30 November 2015, evaluated the efficacy and safety of sofosbuvir plus ribavirin therapy among treatment‐naïve patients with chronic genotype 1 or 3 HCV infection. A total of 117 patients with genotype 1 or 3 HCV infection were randomized 1:1 to receive sofosbuvir 400 mg and weight‐based ribavirin (1000 or 1200 mg) daily for 16 or 24 weeks. Among those with genotype 1 infection, the primary efficacy endpoint of sustained virologic response at 12 weeks post‐treatment (SVR12) was reported in 90% (95% confidence intervals [CI], 73‐98) and 96% (95% CI, 82‐100) of patients following 16 and 24 weeks of treatment, respectively. For patients with genotype 3 infection, SVR12 rates were 100% (95% CI, 88‐100) and 93% (95% CI, 78‐99) after 16 and 24 weeks of therapy, respectively. Adverse events, most of which were mild or moderate in severity, occurred in 69% and 57% of patients receiving 16 and 24 weeks of treatment, respectively. The most common treatment‐emergent adverse events were asthenia, headache and cough. Only one patient in the 24‐week group discontinued treatment with sofosbuvir during this study. Overall, sofosbuvir plus ribavirin therapy achieved SVR12 rates ≥90% and was well tolerated among treatment‐naïve patients with chronic genotype 1 or 3 HCV infection in India.